2014
DOI: 10.5812/ijem.16713
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Acute Kidney Injury in Geriatric Patients Undergoing Total Knee Replacement Surgery

Abstract: Background:Few studies have focused on patients’ characteristics that affects acute kidney injury (AKI) after total knee replacement surgery (TKR).Objectives:The primary objective of this retrospective study was to identify patients’ characteristics associated with AKI after TKR.Patients and Methods:Between January 2008 and December 2009, 659 patients with a mean age of 67.1 years (range, 39-99) underwent TKA at Regional Hospital Knee and Hip Institute. Retrospective chart review was done to identify patients’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 55 publications
0
13
0
1
Order By: Relevance
“…Sehgal et al 9 found an incidence of 21.9% in 659 total joint arthroplasties using AKIN creatinine criteria.…”
Section: Do All Stages Of Kidney Injury Count?mentioning
confidence: 99%
“…Sehgal et al 9 found an incidence of 21.9% in 659 total joint arthroplasties using AKIN creatinine criteria.…”
Section: Do All Stages Of Kidney Injury Count?mentioning
confidence: 99%
“…The impact of statins on AKI due to surgery (Table 4) AKI is common after major elective surgery affecting up to 30% of patients [46][47][48][49][50][51][52] dependent on the type surgery and the age and frailty of the patient group. The main mechanism of post-operative AKI is thought to be impaired perfusion leading to renal ischaemia.…”
Section: 2mentioning
confidence: 99%
“…Major procedures known to be commonly complicated by AKI now include major vascular surgery, liver transplants, esophagogastrectomy, gastric bypass, thoracotomy, liver resections, and total knee replacements. 11,12 As highlighted above, different AKI syndromes occur in varied settings and with a spectrum of risk factors (e.g., rhabdomyolysis) that sometimes advocate for specific therapies.…”
mentioning
confidence: 98%
“…Les interventions majeures connues comme étant souvent compliquées par une IRA incluent dorénavant les chirurgies vasculaires majeures, les greffes hépatiques, l'oesophagogastrectomie, le pontage gastrique, la thoracotomie, les résections hépatiques et les arthroplasties totales du genou. 11,12 Comme nous l'avons souligné ci-dessus, différents syndromes d'IRA surviennent dans différents contextes et sont associés à un éventail de facteurs de risque (par ex., la rhabdomyolyse) qui préconisent des traitements spécifiques.…”
unclassified